Water quality assessment in the Reventado's watershed, Cartago, Costa Rica, oriented to the development of indicators of sustainability - Villegas Osorio, Javier G. (Centro Agronómico Tropical de Investigación y Enseñanza (CATIE), 2014)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica), 1995